The United States - O'Donovan, Patrick Anthony (New York : Time-Life Books, 1968)
Nine essays illustrated with photographs on various aspects of Ameri can civilization and culture, including political history and thought, education, economy, religion, and the Nation's role and influence in th e modern world.
Bibliography: p. 187.
Keywords: United States -- Civilization -- 1945-; United States -- Civilization